Identification of a pathogenicity island, which contains genes for virulence and avirulence, on a large native plasmid in the bean pathogen Pseudomonas syringae pathovar phaseolicola - Jackson, Robert W. (The National Academy of Sciences, 1999)
The 154-kb plasmid was cured from race 7 strain 1449B of the phytopathogen Pseudomonas syringae pv. phaseolicola (Pph). Cured strains lost virulence toward bean, causing the hypersensitive reaction in previously susceptible cultivars. Restoration of virulence was achieved by complementation with cosmid clones spanning a 30-kb region of the plasmid that contained previously identified avirulence (avr) genes avrD, avrPphC, and avrPphF. Single transposon insertions at multiple sites (including one located in avrPphF) abolished restoration of virulence by genomic clones. Sequencing 11 kb of the complementing region identified three potential virulence (vir) genes that were predicted to encode hydrophilic proteins and shared the hrp-box promoter motif indicating regulation by HrpL. One gene achieved partial restoration of virulence when cloned on its own and therefore was designated virPphA as the first (A) gene from Pph to be identified for virulence function. In soybean, virPphA acted as an avr gene controlling expression of a rapid cultivar-specific hypersensitive reaction. Sequencing also revealed the presence of homologs of the insertion sequence IS100 from Yersinia and transposase Tn501 from P. aeruginosa. The proximity of several avr and vir genes together with mobile elements, as well as G+C content significantly lower than that expected for P. syringae, indicates that we have located a plasmid-borne pathogenicity island equivalent to those found in mammalian pathogens.